2014
DOI: 10.1136/bmjopen-2014-005295
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment feasibility to a cohort study of endocrine and metabolic health among survivors of childhood brain tumours: a report from the Canadian study of Determinants of Endometabolic Health in ChIlDrEn (CanDECIDE)

Abstract: ObjectivesThe aim of this study was to test the feasibility of recruitment and performance of study procedures of the Canadian Study of Determinants of Endometabolic Health in ChIlDrEn (CanDECIDE) study, which was designed to assess the determinants of endocrine and metabolic health in survivors of childhood brain tumours.SettingA single paediatric tertiary care centre in Hamilton, Ontario, Canada.ParticipantsWe included boys and girls, aged 5 years and older, who were lean (body mass index (BMI) below 85th ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 49 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Participants were consecutively recruited from McMaster Children’s Hospital (Hamilton), Ontario, Canada from November 2012 to November 2017 to partake in the Canadian Study of Determinants of Endometabolic Health in Children (CanDECIDE study) 58 , 59 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were consecutively recruited from McMaster Children’s Hospital (Hamilton), Ontario, Canada from November 2012 to November 2017 to partake in the Canadian Study of Determinants of Endometabolic Health in Children (CanDECIDE study) 58 , 59 .…”
Section: Methodsmentioning
confidence: 99%
“…Standardized questionnaires were used to collect data on age, sex, puberty, and ethnicity 58 , 59 . Medical records were consulted to verify and collect data regarding tumor type, location, sidedness and treatment modalities for SCBT.…”
Section: Methodsmentioning
confidence: 99%
“…The complete study methodology has been reported previously 76,77 . This is a secondary analysis of cross-sectional data from the Canadian Study of Determinants of Endometabolic Health in Children (CanDECIDE study) 76,77 . The Hamilton Integrated Research Ethics Board has approved this project.…”
Section: Participantsmentioning
confidence: 99%
“…This secondary data analysis used data that were collected as a part of the CanDECIDE Study. This is a cohort study conducted at McMaster Children’s Hospital in Hamilton, Ontario, Canada 52 , 53 .…”
Section: Methodsmentioning
confidence: 99%
“…The collected data included age, sex, ethnicity, puberty, pregnancy gestation, maternal gestational diabetes and preeclampsia, and reported birth weight using standardized questionnaires 52 , 53 . While reported birth weight correlates with measured birth weight 54 , the reported birth weight was verified from the medical records.…”
Section: Methodsmentioning
confidence: 99%